ROLUL FACTORULUI BIOPEDOLOGIC ÎN EVOLUŢIA VERSANŢILOR TÂRNAVEI MARI ÎNTRE COPŞA MICĂ - BLAJ (PANGEEA, 2025)
It is important to present the soils because upon them most of the subairean agents act directly on it; they are first solicitated to diferent processes because they protect the rock and their strength to errosion depends on the rhythm of the slope process. Generally, soils have formed under a vegetal wooden layer, but once with the deforestation, they have suffered a series of transformations. The rock played a special role in the formation of the soil types along with the bio-climatic factors. The research regarding the vegetation from this region which remakes, in some measure, the past of the vegetation in this teritory, shows the dominat presence, from the begining of the cuarternar era, of the Pinus sylvestris forests along with groups of spruces and very little birchs and willows.We can take some conclusions: the forests occupy a reduced surface because of frequent cutting;  there is a process of desertefication of the climate because of the reduction of the natural vegetation and also of the surfaces occupied by forests which determined the appearence of xerophyle phytocenosis inside the herbaceous vegetation which haveless economical importance;  on relatively large surfaces, in specially on medium or large enclined slopes, it was observed an advanced degradation of some vegetal groups and an advanced errosionprocess of the soil;  there must be taken into consideration the rationing of the grazing, the regeneration of the vegetal layer and antierrosion works.